Comparative Numerical Analysis Fatigue Damage Based On Variation In Quantities Mooring Line On Aker Smart 2 FPSO - Aulia, Nur Salsabila; Assidiq, Fuad Mahfud (Maritime Park: Journal of Maritime Technology and Society, 2024)
The Aker Smart 2 FPSO is the second FPSO from the Norwegian FPSO operator: Aker Floating Production, and will operate for Reliance in India. This FPSO will be moored with a mooring system catenary to the seabed. In its operation, the FPSO will be influenced by dynamic loads such as sea waves, ocean currents and wind on the mooring rope structure periodically. This may cause damage to the structure mooring line which influences the performance of the operational structure. The aim of this research is to investigate motion trajectory (surge & sway), mooring line stress, and deterministic fatigue on the mooring system catenary by making comparisons using variations in quantities mooring line. Dimensions mooring line type chain on fairlead with varying amounts mooring line namely 4x1, 4x2, and 4x3 which will then be analyzed fatigue damage-his. Numerical observations of FPSO motion on following seas, stern quartering seas, beam seas, bow quartering seas, and head seas show Response Amplitude Operator from movement surge, sway, heave, roll, pitch, and yaw due to harsh environments with Hs = 2.0 meters and T = 12 seconds. Observation Motion Trajectory it is found that the greater the number mooring line then value DOffset or movement surge & sway will get smaller. Meanwhile, in observation Mooring Line Stress and Fatigue Damage obtained both are directly proportional where the greater the tension mooring line the greater the damage. This is because the mass of the rope used is not proportional to displacement boat. And in this numerical analysis simulation it only reaches the initial movement, namely at 100 seconds, where the ship's condition has not yet reached the stable condition it should be.